Histomorphologic changes after contact transscleral Nd: YAG laser cyclophotocoagulation with scleral compression (Ukrainian Journal of Ophthalmology, 2026)
Introduction. Refractive glaucoma is referred to the most severe forms of the disease.  To reduce intraocular pressure and pain syndrome, transscleral laser photocoagulation of the ciliary body is currently used. Puprose. To determine in experiment morphological changes in the sclera and ciliary body after contact transscleral cyclophotocoagulation (CTS CPC) with scleral compression (SC) using infrared Nd: YAG laser radiation. Material and Methods. Experimental studies involved two rabbits (4 eyes). Nd: YAG laser (λ=1.06 µm) was adapted to a 600 µm fiberoptic crystal probe and used for laser photocoagulation. Laser pulse was 0.7- 1.2 J; laser pulse length was 3 ms. After topical anesthesia with proxymetacaine hydrochloride (0.5%), CTS CPC SC was performed in superior and inferior eyeball quadrants, at 2-3 mm from the limbus in two rows in full circle (360°) with the sclera compressed by a 6 g endface for 5 seconds. Results. The histological studies at Day 1 after CTS CPC SC revealed damage to the pigment epithelium of the ciliary processes and their vessels when laser pulse parameters were low (0.7-1.0 J).  High-energy CTS CPC SC of the ciliary body (1.1-1.2 J) damaged the sub-conjunctival tissue and sclera. With laser radiation, collagen stromal fiber separation and channeling were noted as result of a hydrodynamic shock which can supposedly lead to increased transscleral filtration. The mechanism of antihypertensive action of CTS CPC SC using Nd:YAG laser is likely to include two components: photocoagulation and hydrodynamic cavitation.
Keywords: transscleral cyclophotocoagulation; Nd: YAG laser; ciliary body; sclera; morphological changes